Neurolinguistics and Psychosociolinguistics - Hertomo Miftahudin; Dwi Rizaldi Mualimin; Muhammad Eep Saiful Haq (al-Afkar, Journal For Islamic Studies, 2025)
Language is one of God's gifts that is a human facility to maintain his mind and control external influences that come into contact with him. Humans are social creatures who need interaction with each other. This interaction certainly requires language so that it can be understood by the other person. In general, humans do not feel that the use of language is a skill that requires knowledge. The use of language seems easy because the growth of a person using language seems to run naturally according to age development. For example, when a baby is one to one and a half years old, he begins to produce small forms of language that we can identify as words. The process of language runs mechanically and mentally, meaning that the language process is related to the mental/brain process of humans so that linguistic studies need to be complemented by interdisciplinary studies between linguistics and psychology which are generally called psycholinguistics. The object of psycholinguistics is the language found in humans.